Pengurangan Tarif BPHTB: Strategi Perlindungan Hukum bagi Masyarakat Ekonomi Lemah - Asranita Asranita; Siti Malikhatun Badriyah (CV. Social Politic Genius (SIGn), 2023)
This study aims to examine and analyze the juridical basis for Local Governments in forming regional regulations related to reducing BPHTB rates. This study uses normative legal research with the statute and conceptual approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the Law Number 21 of 1997 has considered fairness by regulating NPOPTKP or NJOPTKP for land and buildings. Moreover, with the enactment of Law Number 1 of 2022, Local Governments are authorized to formulate regional regulations on reducing BPHTB rates for the economically disadvantaged community. Therefore, it is recommended that Local Governments invest in capacity-building initiatives for their tax officials, focusing on policy knowledge, surveillance techniques, and law enforcement. This policy would ensure they are adequately equipped to oversee taxpayer compliance and identify potential violations. Furthermore, there should be continuous engagement with all stakeholders to identify potential obstacles and challenges in policy implementation. Regular evaluations and monitoring are also crucial to assessing the policy’s effectiveness and impact on tax revenue and the economically disadvantaged community. Lastly, taxpayers must understand the changes in BPHTB rates, their rights, and obligations to ensure policy compliance. By doing so, Local Governments can enhance the effectiveness of the BPHTB rate reduction policy and ensure it brings about maximum benefits for the economically disadvantaged community.